The Prevalence and Risk Factors of White Spot Syndrome Virus in Tiger Shrimp at Traditional Ponds (PREVALENSI DAN FAKTOR RISIKO WHITE SPOT SYNDROME VIRUS PADA TAMBAK UDANG WINDU TRADISIONAL) - Taslihan, Arief; Sumiarto, Bambang; Nitimulyo, Kamiso H. (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
A research has been conducted to determine the status of the White Spot Syndrome Virus (WSSV)epidemic on traditional shrimp ponds in Demak regency. A cross-sectional research method was selected,by calculating samples using statistical calculation based on the assumption of 70% prevalence rate anderror (p<10%). Additionally, this research also determined the risk factors in the onset of WSSV shrimppond. Surveyed areas included Sayung and Bonang, subdistrict in Demak district, because the area areactively engaged with shrimp farming. A total of 90 traditional tiger shrimp ponds were sampled in thisstudy. The results showed that the prevalence of WSSV infected farms was 65.6% (Confident Interval,CI=55.7%-75.4%). Factors that affected high prevalence of WSSV were screening of seed (Coefficient=1.517,P<0.049), pond size (coefficient=0.0002, P<0.0089) and drying ponds (coefficient=3.756, P<0.001). Factorsthat affected the production of shrimp in ponds were analysed using multivariate regression analysis.Based on the analysis, some factors had an important role in production, i.e. : stadia of shrimp seed(coefficient=19.091, P<0.19), water depth in pond (coefficient=1.343, P<0.0024) and WSSV-infected shrimp(coefficient=-44.369, P<0.001). It was concluded that WSSV prevalence in studied area was 65.6%, and itconsidered as hyperendemic. Factors affected the WSSV prevalence were selection of seed, pond’s size anddrying ponds. Risk factors affected shrimp production in the pond were stocking seed stadia, whereasWSSV-infection of shrimp was negatively affected factor.
Keywords: WSSV infection risk factors , traditional farms , prevalence, Penaeus monodon